Application And Performance Of Arduino-Based Idle Stop System On Carburetor Engine - Putut Son Maria; Taufik Setiyadi (PROtek : Jurnal Ilmiah Teknik Elektro, 2026)
Efforts to conserve fuel oil (BBM) promoted by the Indonesian government and many other countries are motivated by the fact that fossil fuel availability has decreased and environmental pollution continues to worsen. Strategies for utilizing fuel resources include conservation and the development of alternative fuels. Vehicle manufacturers have attempted to develop vehicles with IDSS (idling start-stop system) or SSS (start-stop system) technology, which are claimed to be more fuel-efficient. However, products with these features are only available in newer vehicles equipped with injection systems. To enable its application on conventional engines of which continues to utilize carburetors, an ISS (Idle Stop System) based on comparable IDSS and SSS systems was designed and tested in this study. Speed sensors, crankshaft sensors, and temperature sensors were used as inputs for the Arduino, which serves as the control for engine startup or shutdown. Test results indicate that the ISS (idle stop system) functions effectively, achieving fuel savings of 4.65–7.56% under test conditions on a 28-kilometer test track.